Pengaruh Return on Assets, Pertumbuhan Penjualan, Current Ratio, dan Ukuran Perusahaan terhadap Struktur Modal: Studi Empiris pada Perusahaan Sub Sektor Farmasi yang terdaftar di Bursa Efek Indonesia Periode 2019-2025 - Julian Fajar Anandiko; Ivo Rolanda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The pharmaceutical subsector is one of the strategic sectors within the healthcare and manufacturing industries that plays an important role in supporting national health resilience and Indonesia's economic growth. The growth of this industry requires companies to manage their sources of financing optimally in order to support operational sustainability and business expansion. This study aims to examine the effect of Return on Assets (ROA), Sales Growth, Current Ratio (CR), and Firm Size on Capital Structure. This study employed a quantitative research method with purposive sampling based on predetermined criteria. The population consisted of 15 pharmaceutical subsector companies listed on the Indonesia Stock Exchange, while the sample comprised 9 companies that met the research criteria, resulting in a total of 63 observations during the 2019–2025 period. Data were analyzed using panel data regression with the assistance of SPSS version 26 and Microsoft Office Excel 2024. The results indicate that Return on Assets (ROA) and Firm Size have no significant effect on Capital Structure, as measured by the Debt-to-Equity Ratio (DER). In contrast, Sales Growth has a positive and significant effect on Capital Structure (DER), while the Current Ratio (CR) has a negative and significant effect on Capital Structure (DER).